2021
DOI: 10.1021/acssuschemeng.1c05117
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Oxygenation Performance of a Cyanobacterial Lipoxygenase by Oxygen Channel Engineering

Abstract: Lipoxygenase catalyzes the dioxygenation of unsaturated fatty acids, which represents a sustainable pathway for producing bioderived fine chemicals. Herein, structure-guided engineering of the oxygen tunnel of a well-expressed 13-(S)-lipoxygenase from cyanobacteria was performed, resulting in a mutant A324G/S392G which showed 3 to 5-fold increases in activity toward a panel of unsaturated fatty acids. Molecular dynamics simulations elucidated the molecular basis for A324 and S392 as activity determining residu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 51 publications
0
10
0
Order By: Relevance
“…Potentially, if the gas channel was occupied by another nonsubstrate gas, the enzyme activity would lose rapidly and irreversibly. It has been reported that the oxidation performance of oxygenase could be improved by oxygen channel engineering . In Figure c, NOX was first bubbled with O 2 for 6.5 h, and the NOX activity decreased from 100 to 85%.…”
Section: Resultsmentioning
confidence: 84%
See 2 more Smart Citations
“…Potentially, if the gas channel was occupied by another nonsubstrate gas, the enzyme activity would lose rapidly and irreversibly. It has been reported that the oxidation performance of oxygenase could be improved by oxygen channel engineering . In Figure c, NOX was first bubbled with O 2 for 6.5 h, and the NOX activity decreased from 100 to 85%.…”
Section: Resultsmentioning
confidence: 84%
“…It has been reported that the oxidation performance of oxygenase could be improved by oxygen channel engineering. 20 In Figure 5c, NOX was first bubbled with O 2 for 6.5 h, and the NOX activity decreased from 100 to 85%. Following N 2 bubbling, the NOX activity decreased slowly from 85 to 14% after 28 h, and the activity loss was notably slower compared with Figure 5b, which might indicate that the oxygen channel of NOX was first occupied and saturated by O 2 ; therefore, the dissolved N 2 would not take over the active site of NOX, and only the N 2 −water interface affected the deactivation of NOX.…”
Section: ■ Results and Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Changing the enzyme specificity from 9R-to almost exclusively 13S-dioxygenation or vice versa was achieved in some bacterial LOXs by exchanging the Coffa site residue for a bulkier amino acid residue (Andreou et al, 2008;Newie et al, 2016;Yi et al, 2020). Improving the enzyme activity by enlarging the oxygen channel through structure-guided engineering (Ala324Gly/ Ser392Gly double substitution) has been reported recently (Qi et al, 2021).…”
Section: Enzyme Improvement Approachesmentioning
confidence: 99%
“…Lipoxygenase (EC. 1.13.11.12, LOX) mainly catalyzes the dioxygenation of polyunsaturated fatty acids with one or more cis , cis -1, 4-pentadiene units to produce hydroperoxy fatty acids [ 1 ], which are used in the food, chemical, and textile industries [ 2 , 3 ]. Presently, most of the applied research is based on LOX extracted form soybean [ 4 ].…”
Section: Introductionmentioning
confidence: 99%